A new species of the rare Gabritini (Hemiptera: Cicadellidae: Coelidiinae) from Parque Nacional Serra das Confusões, Northeastern Brazil - Barbosa, Julianna Freires; Gonçalves, Clayton Corrêa; Takiya, Daniela Maeda (Zootaxa, 2023)
A new species of the genus Gabrita Walker, 1858 is described, from Parque Nacional Serra das Confusões, Piauí, representing the first record of Gabritini for the Northeastern Region of Brazil. Gabrita confusa sp. nov. is easily recognized by the long process arising on the shaft of the aedeagus, absent in other species of the genus. A distribution map and a key to the six known species of Gabrita are provided.